Thank you Spore readers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
With only two issues under its belt, SPORE has already received more than a hundred letters of encouragement from its readers, including many from ACP countries. We thank them all for both their support and their contributions. SPORE's objective is...